2013
DOI: 10.1590/s0100-736x2013001200013
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic evaluation of Crioulo horses participating in competitions of 750 km

Abstract: RESUMO.-[Avaliação metabólica de cavalos Crioulos submetidos a uma competição de resistência de 750 km.] O cavalo Crioulo realiza uma das provas de maior exigência física nas modalidades equestres. A Marcha de Resistência é uma competição na qual os animais percorrem 750km durante 15 dias. O objetivo desse estudo foi caracterizar as respostas metabólicas ocorridas nesse período. Foram avaliados 11 equinos da raça Crioula inscritos na competição, sendo dois machos e nove fêmeas. Foram efetuadas coletas de sangu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(10 reference statements)
0
2
1
Order By: Relevance
“…Creatine kinase concentration in both males and females was smaller in this study than reported previously in healthy Crioulo horses in pasture and exercise conditions (Da Cás et al, 2000;Lacerda et al, 2006;Amaral et al, 2013) and in other breeds (Stuchi et al, 2019). Creatine kinase is an enzyme related to muscle function.…”
Section: Resultscontrasting
confidence: 62%
See 2 more Smart Citations
“…Creatine kinase concentration in both males and females was smaller in this study than reported previously in healthy Crioulo horses in pasture and exercise conditions (Da Cás et al, 2000;Lacerda et al, 2006;Amaral et al, 2013) and in other breeds (Stuchi et al, 2019). Creatine kinase is an enzyme related to muscle function.…”
Section: Resultscontrasting
confidence: 62%
“…This differs from the 750-km gait competition, where animals have less time to prepare. Another study by our research group on Crioulo horses in Freio de Ouro identified higher values of CK and LDH before starting the competition than at the end, indicating higher physical demand within seven days prior (Amaral et al, 2013).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation